ヒガシ ナンキョク タイリク ノ ラヒョウ イキ カラ サイシュウ サレタ カザン バイ ヲ フクム ヒョウソウ ノ シゼン ザンリュウ ジキ - 船木, 箕; フナキ, ミノル; Funaki, Minoru (1990)
P(論文) 東南極サウスビクトリアランドのアランヒルズ, 東クィーンモードランドのやまと山脈及びセールロンダーネ山脈の裸氷域表面から採集された5試料の火山灰を含む氷(dirt-ice)の持つ自然残留磁気(NRM)の性質を調べた。これらの試料は1.38-22.1×10^<-7>Am^2/kgの磁化強度を持ち, 交流消磁に対し少なくとも50mTまで安定であった。NRMは肉眼で認められるdirt-ice層にのみ認められ, いわゆる普通の南極氷からは, 意味ある磁気は測定されなかった。Dirt-ice層内でのNRMの方向は一定であったが, その強度は試料によって, また層内の場所によって異なった。方向の記録された試料の持つNRMの方向は, 採集地点の現在の地磁気方向とほとんど同じであった。このことは, dirt-ice層中の磁性粒子が, 太陽ふく射による粒子周辺の氷の融解により回転し, そのNRMが現在の地磁気方位に再配列した可能性を示している。 Natural remanent magnetizations (NRMs) of 5 dirt-ice layers including tephra collected from the Allan Hills in Southern Victoria Land, the Yamato Mountains and the Sφr Rondane Mountains in Eastern Queen Maud Land, East Antarctica, were investigated. The NRMs with 1.38 to 22.1×(10)^<-7>Am^2/kg in intensity were very stable against AF demagnetization at least up to 50mT. The magnetic layers consisted with the dirt-ice layers recognized by the naked eye, but magnetizations in the clear-ice were weak for any significant measurements. The uniform NRM directions were obtained in the dirt-ice layers with upward directions. Those of the oriented 2 samples (A, E) were almost parallel to the present geomagnetic field direction in situ. So, a possible mechanism is rearrangement of the magnetic grains adjusting the NRM directions to the geomagnetic field direction due to partial melting of the ice around the grains by the solar radiation. departmental bulletin paper